Performing electronic music live - Hermes, Kirsten (Audio Engineering Society presents., 2022)
"This comprehensive book lays out the conceptual approaches, tools and techniques for performing electronic music, from DJing, DAWs, MIDI controllers, traditional instruments, live sound design, hardware setups, custom software and hardware to live visuals, venue acoustics and live show promotion. Via the companion website, performingelectronicmusic.live, readers can expand on their knowledge with hands-on video tutorials for each chapter. Live music is exhilarating - it creates life-changing experiences and powerful emotions. Technology can make us feel empowered, enable us to overcome limiting beliefs and allow us to achieve a high level of creative expression, no matter our background or skillset. The options are virtually endless, ranging from laptop setups to new instruments built from scratch. Through case studies and contrasting tutorials by successful artists, Kirsten Hermes guides us through many different ways in which you can create memorable experiences on stage. This is backed up with historic and scientific facts ranging from psychology to marketing. The book also features interviews with highly accomplished musicians and practitioners, including superstar trance DJ Alex M.O.R.P.H., BBC Audio R&D and live show designer Laura Escudé, who has worked with Kanye West, Missy Elliot and Herby Hancock. The book is not a dogmatic to-do list, but rather, it explores many contrasting examples of successful approaches, to help you turn overwhelm into inspiration. Whether you are a student, hobby producer or a more advanced performer, this book gives you a comprehensive overview over your options. Students of music production courses, particularly at postgraduate level, but also researchers in the field of creative-focused performance technology will find this to be a useful, all-encompassing resource, with many starting points and resources for a deeper creative exploration"--